Caregivers Burnout in Pediatric Laryngomalacia; The role of clinizcal and psychological factors - ÖZAYDIN, AYŞE NİLÜFER (My University, 2023)
Introduction: This study aims to assess caregiver burnout in relation to children diagnosed with laryngomalacia and identify factors influencing burnout levels. Materials and methods: A cohort of 101 caregivers of children with laryngomalacia was studied. Burnout was assessed using the Zarit burden interview (ZBI), while the Hamilton anxiety and Hamilton depression scales were employed to gauge psychological distress. The relationship between burnout and variables like the severity of laryngomalacia, the presence of comorbidities, the child's age, and caregiver demographics was examined using statistical tools in SPSS Statistics version 28.0 (IBM Corp., Armonk, NY, USA). Results: Caregiver burnout decreased as the child's age increased. A direct correlation was observed between the severity of laryngomalacia and caregiver burnout. The presence of comorbidities in children increased caregiver burnout. Moreover, caregivers with increased levels of depression and anxiety exhibited higher burnout levels. No significant correlation was found between caregiver burnout and socioeconomic status or educational level. Conclusion: The severity of laryngomalacia, the child's age, the presence of comorbidities, and caregivers' psychological health are significant influencers of caregiver burnout. Healthcare professionals should offer targeted support to caregivers, addressing both their physical and psychological needs.
Keywords: Tıp; Dahili Tıp Bilimleri; Halk Sağlığı; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Public Health; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEALTH CARE SCIENCES & SERVICES; MEDICINE, GENERAL & INTERNAL; Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Genel Sağlık Meslekleri; Gözden Geçirme ve Sınav Hazırlığı; Patofizyoloji; Liderlik ve Yönetim; Temel Bilgi ve Beceriler; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Değerlendirme ve Teşhis; Dahiliye; Sağlık Politikaları; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); General Health Professions; Review and Exam Preparation; Pathophysiology; Leadership and Management; Fundamentals and Skills; Community and Home Care; Care Planning; Assessment and Diagnosis; Internal Medicine; Health Policy; Family Practice; Medicine (miscellaneous); General Medicine; Pediatrics; Otolaryngology